Analisis Pemilihan Supplier Bahan Baku di Rumah Makan dengan Metode Analytic Hierarchy Process - Achmad, Alfin Hidayat; Kartika, Nurullaily Kartika (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2025)
The Food and Beverage industry is a business that is growing and growing every year. Along with the development of the times, which is used by selecting the best supplier for the Rumah Makan Bumas Masakan Jawa to conduct supplier selection which becomes a decision-making problem that includes qualitative decisions This study seeks to analyze the criteria that influence the selection of suppliers and determine the best by using the analytic hierarchy process (AHP) method at the Rumah Makan Bumas Masakan Jawa. The research results obtained with AHP method based on the results of the suppliers weighting of the criteria and sub criteria, the first place is Redzer with an overall value 0.565. In the second place is UD Anak Lanang suppliers with an overall value 0.238. In the last order is UD Bimantara with an overall value 0.197.